Leveraging ChatGPT to enhance students’ writing skills, engagement, and feedback literacy - Oktarin, Irene Brainnita; Edistianda Eka Saputri, Maria; Magdalena, Betty; Hastomo, Tommy; Maximilian, Aksendro (Edelweiss Applied Science and Technology, 2024)
The rapid development of technology has dramatically increased the use of AI chatbots in English Language Teaching (ELT). This research investigates the role of AI chatbots in English as Foreign Language (EFL) students’ writing by addressing the following three main goals: (1) to measure how AI chatbots affect students' writing learning outcomes, (2) to evaluate their impact on writing feedback literacy and engagement, and (3) to explore how students use AI chatbots to improve these areas. Fifty Indonesian university students undertaking an Economic English course participated in this mixed-methods study, divided into an experimental group and a control group, each with 25 students. Data collection instruments included tests, questionnaires, and interviews. Quantitative data were analyzed statistically, while qualitative data were examined through thematic analysis. The findings revealed that the experimental group using AI chatbots showed significant improvements in writing outcomes. Additionally, this group demonstrated notable advancements in both writing feedback literacy and engagement. Students employed various strategies such as interactive writing practice, personalized learning plans, guidance on reading materials, acting upon feedback, peer feedback, gamified learning, and community building to enhance these areas. These results advance our understanding of the role of AI chatbots and inform instructional strategies in ELT.